2007
DOI: 10.1097/ijg.0b013e31802b3527
|View full text |Cite
|
Sign up to set email alerts
|

No Increased Risk of Developing Alzheimer Disease in Patients With Glaucoma

Abstract: POAG was not associated with increased risk of developing AD. It cannot be excluded that this negative finding is due to diagnostic misclassification as register data were used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
102
1
7

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(114 citation statements)
references
References 19 publications
4
102
1
7
Order By: Relevance
“…[15][16][17] In a longitudinal study using nationwide case register data of patients who had been hospitalized in Denmark, Kessing et al 15 found that OAG was not associated with an increased risk of subsequent AD. However, the cases and controls were not matched in terms of sociodemographic characteristics or medical comorbidities, and there may have been a selection bias for patients with more-severe OAG.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[15][16][17] In a longitudinal study using nationwide case register data of patients who had been hospitalized in Denmark, Kessing et al 15 found that OAG was not associated with an increased risk of subsequent AD. However, the cases and controls were not matched in terms of sociodemographic characteristics or medical comorbidities, and there may have been a selection bias for patients with more-severe OAG.…”
Section: Discussionmentioning
confidence: 99%
“…12 However, previous epidemiologic studies focusing on the association between OAG and dementia showed inconsistent results. [13][14][15][16][17] There are only four nationwide or population-based studies in Western countries, [15][16][17][18] and, to the best of our knowledge, large epidemiologic investigations regarding the association between OAG and dementia are still lacking in Asian populations. Therefore, the aim of this study was to explore the association between OAG and dementia in an ethnic Chinese (ie, Taiwanese) population by means of a case-control design using a large, nationwide population-based data set in Taiwan.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, in a large Danish study, no association was found between POAG and AD. 203 Abnormal tau proteins have also been observed in the retina and optic nerve in AD, FTD, and in glaucoma. 204 There is a decline in the density of optic nerve axons in AD.…”
Section: Optic Nervementioning
confidence: 99%
“…Results were skewed by the largest study, but even when excluded, there was still high heterogeneity. The two largest studies 57,58 in this review showed a protective association between AD and glaucoma, whereas the smaller studies suggested greater risk. Methodology varied; half of the studies evaluated both diseases crosssectionally, 51,53,55,59,60 limiting ability to make conclusions about causality and progression.…”
mentioning
confidence: 97%